Arctic Summer Cloud Ocean Study (ASCOS) - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 31 July to 12 September 2008 - Arctic Summer Cloud Ocean Study - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 31 July to 12 September 2008. - Swedish Polar Research Secretariat (Swedish Polar Research Secretariat, 2017)
The project Arctic Summer Cloud Ocean Study (ASCOS) was an international research expedition to the Arctic ocean. The Swedish icebreaker Oden served as the platform for the research carried out in the sea, on the glacier and on land.
ASCOS left Longyearbyen on Svalbard in early August 2008 on the Swedish icebreaker Oden, heading for the central Arctic Ocean. To understand cloud formation a number of scientific specialties are needed, therefore ASCOS is genuinely interdisciplinary.The observations in ASCOS covered a column from 400 meters into the ocean, up through the troposphere; the lowest 8-12 km of the atmosphere where clouds and weather occurs.
The plan was to spend as much time as possible in the central Arctic pack ice. Therefore Oden anchored in the pack ice to the ice floe, drifting with the ice for almost three weeks while taking detailed observations of processes determining the formation and life-cycle of clouds.

Purpose:

The goal of ASCOS was to increase our knowledge of clouds over the central Arctic Ocean by studying processes that are important to their formation and occurrence. This was achieved through interdisciplinary studies in which cloud formation was linked to the microbiological life in the ocean and ice, by means of detailed observations made from several hundred metres below the ocean’s surface to many kilometres up in the atmosphere.

This data set contains meteorological, oceanographic and ship data collected during the expedition Arctic Summer Cloud Ocean Study (ASCOS), which was an international research cruise using the icebreaker Oden in the Arctic Ocean. The data were measured during the 40 days that Oden was cruising in the Arctic Ocean close to the north pole.Data includes meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.Ship data: Position, Speed, Course.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.

Arctic Summer Cloud Ocean Study var en forskningsexpedition som 2008 gick till Arktiska havet med den svenska isbrytaren Oden. Studiens fokus var de fysiska och kemiska processerna som leder till molnbildning. ASCOS var den fjärde forskningsexpeditionen till centrala Arktis för att bedriva atmosfärisk forskning. De tidigare expeditionerna ägde rum 1991, 1996 och 2001.
Expeditionen startade i Longyearbyen på Svalbard 1 augusti och återvände till samma plats 9 september. Den centrala delen av expeditionen, som blev en stor framgång, bestod av en tre veckor lång isdrift, då Oden förankades till och drev med ett 3x5 km stort isflak. Mätningar från ~400 m ned i havet och upp genom hela troposfären (de första 8-12 km av atmosfären där moln och väder förekommer) genomfördes då, från Oden, från isen och med helikopter.

Syfte:

Syftet med ASCOS var att tillhandahålla data som gör det möjligt att bättre modellera moln i klimatmodeller för Arktis. Dessa moln är av största vikt för energibalansen vid ytan och därmed för smältning och frysning av havsisen. I Arktis fann man att de små luftburna partiklar som varje droppe eller iskristall måste bildas på under sommaren oftast kommer från biologiska processer i det öppna vattnet mellan de smältande isflaken. För att förstå hur detta går till, och vilka konsekvenser ett ändrat klimat kan ha på dessa processer, var ASCOS med nödvändighet tvärvetenskapligt, och samlade experter i marinbiologi, kemi, oceanografi, atmosfärkemi, aerosolfysik, kemi samt meteorologi.

This data set contains meteorological, oceanographic and ship data collected during the expedition Arctic Summer Cloud Ocean Study (ASCOS), which was an international research cruise using the icebreaker Oden in the Arctic Ocean. The data were measured during the 40 days that Oden was cruising in the Arctic Ocean close to the north pole.Data includes meteorological variables: Air temperature, Humidity, Wind direction/speed, Atmospheric pressure.Oceanographic variables: Sea water temperature, Conductivity, Salinity and Sound velocity.Ship data: Position, Speed, Course.

Quality Information:

Obviously erroneous data (e.g. negative air pressure) have been omitted. No other processing or quality check of the data has been undertaken. Users should be aware of this in further data handling and analysis.
Arctic Summer Cloud Ocean Study (ASCOS) - Meteorologiska och oceanografiska data, samt skeppsdata, insamlade ombord på isbrytaren Oden från 31 juli till 12 september 2008 - Arctic Summer Cloud Ocean Study - Meteorological, Oceanographic and Ship Data Collected Onboard Icebreaker Oden during 31 July to 12 September 2008.
Keywords: Meteorology; Meteorologi; ATMOSPHERE; ATMOSPHERIC WINDS; SURFACE WINDS; ATMOSPHERIC TEMPERATURE; ATMOSPHERIC WATER VAPOR; HUMIDITY; ATMOSPHERIC PRESSURE; SURFACE PRESSURE; OCEANS; SALINITY; CONDUCTIVITY; OCEAN TEMPERATURE; SEA SURFACE TEMPERATURE; The icebreaker Oden; Isbrytaren Oden; Environmental Sciences; Miljövetenskap; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Engineering and Technology; Teknik; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi; Oceans; Kust och hav; Environment; Miljö